Characterization of Black Sesame (Sesamum indicum L.) Genotypes through Capsule Morphology - JG SAVALIYA; CA BABARIYA; JB PATEL (Seed Research, 2026)
An experiment was carried out at the Sagdividi Farm, Department of Seed Science and Technology,Junagadh Agricultural University, Junagadh, to characterize forty black sesame genotypes based on themorphological characters of the capsule. The genotypes were grouped based on the capsule hairiness into threegroups namely absent (3 genotypes), sparse (30 genotypes) and dense (7 genotypes). Based on the number oflocules per capsule two groups were made i.e., four locules per capsule in (37 genotypes) and six locules percapsule in (3 genotypes). Based on the capsule shape, genotypes were grouped into tapered (13 genotype),narrow oblong (9 genotypes) and broad oblong (18 genotypes) types. Based on the number of capsules per leafaxil, genotypes were grouped into one (36 genotypes) and more than one (4 genotypes) capsules per leaf axil.Based on capsule arrangement, genotypes were grouped into alternate (13 genotypes), opposite (25 genotypes)and cluster (2 genotypes) types. Based on variation in number of capsules per plant, genotypes were groupedinto two categories as, moderate (33 genotypes) and less (7 genotypes). Based on variation in capsule length,genotypes were grouped into two categories as medium (30 genotypes) and long (10 genotypes). Based on thebeak of capsule, genotypes were grouped as, short (14 genotypes) and long (26 genotypes) beaked types.